Assessing catastrophic health expenditure and impoverishment in adult asthma care: a cross-sectional study of patients attending six public health clinics in Klang District, Malaysia - Hussein, Norita; Ng, Chiu Wan; Ramli, Rizawati; Liew, Su May; Hanafi, Nik Sherina; Lee, Ping Yein; Cheong, Ai Theng; Ghazali, Sazlina Shariff; Pinnock, Hilary; Stoddart, Andrew; Schwarze, Jürgen; Khoo, Ee Ming (BioMed Central, 2024)
Background In Malaysia, asthma is a common chronic respiratory illness. Poor asthma control may increase out-of-pocket payment for asthma care, leading to financial hardships Malaysia provides Universal Health Coverage for the population with low user fees in the public health system to reduce financial hardship. We aimed to determine out-of-pocket expenditure on outpatient care for adult patients with asthma visiting government-funded public health clinics. We examined the catastrophic impact and medical impoverishment of these expenses on patients and households in Klang District, Malaysia.